Hypercalcemia Due to Giant Cell Myocarditis: A Case Report. (December 2013) - Patel, Ami M.; Jessup, Mariell; Tomaszewski, John; Doyle, Alden
Granulomatous diseases are a rare cause of hypercalcemia. The pathogenesis is presumed to be from endogenous production of 1, 25-dihydroxyvitamin D by activated macrophages in granulomatous lesions, which harbor the 1 α-hydroxylase enzyme. Herein the first case of hypercalcemia associated with giant cell myocarditis, an unusual type of granulomatous process, is reported. In this case, a patient with giant cell myocarditis had development of progressive heart failure and cardiorenal syndrome that required biventricular support. One year later, hypercalcemia associated with a relatively high 1, 25-vitamin D level and a concomitantly suppressed parathyroid hormone level developed in the presence of stage 4 chronic kidney disease. Her other workup of hypercalcemia was unrevealing for vitamin D intoxication and multiple myeloma. Computed tomography of her chest showed no signs of hilar lymphadenopathy. Her calcium levels returned to normal with low-dose steroid therapy and have remained normal following a successful heart transplant. This case illustrates an unusual cause of hypercalcemia thought to be due to extrarenal calcitriol production associated with giant cell myocarditis.